Cardiovascular Function of Modern Pigs Does not Comply with Allometric Scaling Laws - Gerard J. van Essen; Maaike te Lintel Hekkert; Oana Sorop; Ilkka Heinonen; Jolanda van der Velden; Daphne Merkus; Dirk J. Duncker (NATURE PUBLISHING GROUP, 2022)
Growing concerns have been expressed regarding cardiovascular performance in modern farm pigs, which has been proposed as a critical factor contributing to the reduced adaptability of modern pigs to stress. Here we tested the hypothesis that cardiac dimensions and pump function in modern heavy farm pigs are disproportionally low for their body weight, and investigated potential underlying mechanisms. The results from the present study indeed demonstrate disproportionally low values for stroke volume and cardiac output in pigs with bodyweights over 150 kg. Importantly, these low values were not the result of impaired left ventricular (LV) systolic contractile function, but were due to a disproportionally small LV end-diastolic volume. The latter was associated with changes in determinants of LV passive stiffness, including (i) an increase in LV myocardial collagen, (ii) a shift from the compliant N2BA titin isoform towards the stiff N2B, and (iii) a marked elevation of aortic blood pressure. Taken together, these results demonstrate reduced pumping capacity of the hearts of heavy modern pigs, due to structural abnormalities in the LV myocardium.